THE IMPACT OF USING SINGING ACTIVITIES IN ENHANCING READING SKILLS AMONG KINDERGARTEN STUDENT: A CASE STUDY IN PUTRAJAYA - Hamzah, Rashid Bin (Selangor Humaniora Review, 2024)
This case study investigates the relationship between singing activities and the improvement of reading skills among kindergarten students. The primary aim is to determine whether there is a significant difference in the percentage of scores between pre-tests and post-tests in recognizing open syllables, closed syllables, words, and simple sentences. The subject of the study is a six-year-old male kindergarten student in Putrajaya. The research methodology includes a pre-test conducted before the introduction of singing activities and a post-test administered two weeks later to evaluate the effectiveness of these activities. Observations of the student's behavior during both tests and interviews with the parents before and after the intervention were also conducted. The findings reveal a notable improvement in the respondent's reading skills, with higher scores in recognizing syllables, words, and sentences post-intervention. The respondent also demonstrated increased interest and engagement in reading activities following the introduction of singing. This study suggests that singing activities can effectively enhance early reading skills and foster a positive attitude towards reading.